LANDSCAPE COMPLEXES OF CONES OF MIDDLE ZARAFSHAN (Scientific journal of the Fergana State University, 2023)
In this article on the basis of research methods of field expeditions, geographical information systems, analysis of bibliographic literature cone-shaped plain landscape complexes with unique natural conditions in Middle Zaravshan are analyzed in terms of their natural conditions, occurrence, formation and their use in the economy. As a result, the cone-shaped reversal allowed to evaluate the landscape complexes in terms of their utilization in the sectors of the economy.